A split face randomized controlled trial comparing 1, 064 nm Q‐switched Nd‐YAG laser and modified Kligman's formulation in patients with melasma in darker skin. (5th October 2020) - Dev, Tanvi; Sreenivas, Vishnubhatla; Sharma, Vinod K.; Sahni, Kanika; Bhari, Neetu; Sethuraman, Gomathy
Abstract: Background: No randomized studies compared the efficacy and safety of modified Kligman's triple combination (TC) with 1, 064 nm Q‐switched Nd‐YAG laser (QSNYL) in melasma in darker skin. Objectives: To compare the efficacy and safety of QSNYL and TC in the treatment of melasma in Fitzpatrick skin types IV and V. Methods: In this split face randomized controlled trial, participants' cheeks were randomized to receive either weekly QSNYL (group A) or daily TC (group B) for 12 weeks, followed by 12 weeks of follow‐up. Results: Twenty‐eight patients completed the intervention, and 21 of them completed follow‐up. We found a significant but modest reduction in mean melanin index, modified Melasma Area Severity Index (MASI), and photographic and patient's assessment in both modalities ( P < 0.01). No significant differences were detected between the groups. All patients had reappearance of pigmentation by the end of follow‐up. Adverse reactions were significantly more in group B ( P < 0.001). Limitation: The desired sample size could not be achieved. Conclusion and Relevence: No statistically significant differences were observed between QSNYL and TC as monotherapy in melasma. Reappearance of melasma is inevitable after stopping treatment.